Systematic Literature Review: Determinants, Impact, and Dynamics of Dividend Policy - Galih Hanofa Arya Putra; Sri Lestari; Dian Purnomo Jati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This systematic literature review (SLR) aims to explore the determinants and impact of dividend policy across different markets and industries. By analyzing ten peer-reviewed articles, this study identifies key factors influencing dividend policy, such as profitability, ownership structure, managerial ability, and institutional context. It also examines the role of dividends in managing firm performance and value, mitigating earnings management, and maintaining investor confidence. The findings emphasize that dividend policy plays a pivotal role in shaping corporate strategies and governance.